2015
DOI: 10.15376/biores.11.1.944-956
|View full text |Cite
|
Sign up to set email alerts
|

Shear Strength of Scots Pine Wood and Glued Joints in a Cold Climate

Abstract: The impact of cold temperatures on the shear strength of Scots pine (Pinus sylvestris) joints glued with seven commercially available adhesives was studied in this work. The cold temperatures investigated were: 20, −20, −30, −40, and −50 °C. Generally, within the temperature test range, the shear strength of Scots pine solid wood and wood joints were more resistant to the effect of temperature than those of Norway spruce. As the temperature decreased, only some of the joints' shear strength significantly decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…In these cases, the design must compensate for the different movements of components while maintaining structural integrity. Good performance of glue lines at high temperatures has been documented (Frangi et al 2004;Falkner and Teutsch 2006;Clauss et al 2011;Wang et al 2016). However, although some studies of wooden bridges in cold climates have been reported, there is not much information about the stability of glue lines at low temperatures, especially extreme cold temperatures (Kainz and Ritter 1998;Wacker 2003Wacker , 2009.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…In these cases, the design must compensate for the different movements of components while maintaining structural integrity. Good performance of glue lines at high temperatures has been documented (Frangi et al 2004;Falkner and Teutsch 2006;Clauss et al 2011;Wang et al 2016). However, although some studies of wooden bridges in cold climates have been reported, there is not much information about the stability of glue lines at low temperatures, especially extreme cold temperatures (Kainz and Ritter 1998;Wacker 2003Wacker , 2009.…”
Section: Introductionmentioning
confidence: 98%
“…Wood construction in these areas is frequently exposed to low temperatures for long periods of the year. However, thermal conditions are often not taken into account in the design and estimation of the service life of wood constructions (Wang et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is a lack of studies regarding the influence of the freezing and thawing process on the strength of heat-treated wood dowel joints. This process can affect the mechanical properties of the joints due to the micro-cracks that occur in the cell wall structure during the freezing process and in the adhesive film as well [16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The shear strengths of the glue lines declined gradually through testing with polyvinyl acetate (PVA) and MUF/UF adhesives, but the performance of the PUR adhesive was constant. Wang et al (2016) evaluated the shear strength of Scots pine wood and its glued joints in a cold climate with various adhesives. They concluded that as the temperature decreased from 20 °C to -50 °C, the shear strength of the tested PUR bond lines decreased by only 5.8%.…”
Section: Introductionmentioning
confidence: 99%